Pituitary Carcinoma in a Bitch: Clinical, Tomographic, Histopathological and Immunohistochemistry Findings - Tavares, Flávia; Cobucci, Gustavo Carvalho; Anjos, Denner Santos dos [UNESP]; Fonseca-Alves, Carlos Eduardo; Guimarães, Thais Ferreira; Campos, Simone Neves de (Universidade Federal do Rio Grande do Sul, 2022)
Background: Primary pituitary carcinoma is rarely reported in dogs and only few reports describe its malignancy. In veterinary literature, primary pituitary carcinomas correspond up to 2.4% to 3.4% of intracranial neoplasms found in dogs and information regarding its biological behavior is quite limited. In humans, primary pituitary carcinomas represent less than 1.0% of all tumors found in the pituitary gland. The proposed classification for pituitary carcinoma in humans and dogs determines that the tumor must have its origin in adenohypophyseal region and disseminated metastasis by cerebrospinal fluid or systemically to other organs must be observed. In dogs, a few reports have described primary pituitary carcinoma. The goal of this report was to describe clinical, tomographic, histopathological and immunohistochemistry features of a bitch with primary pituitary carcinoma with adjacent invasion. Case: A 7-year-old female spayed Golden Retriever dog was assessed by general practice due progressive weight loss, muscular atrophy, lethargy, blindness, head pressing, and hyporexia for 21 days. Computed tomography (CT) showed a cerebral parenchyma with expansive extra-axial base formation, originating from sella turcica topography, measuring about 2.0 cm dorsally, displacing the third ventricle, suggesting the diagnosis of pituitary neoplasia. The hormones thyroid-stimulating hormone (TSH) and total thyroxine (T4) as well as stimulation ACTH test were unremarkable. After 7 days, neurological clinical signs progressed and unfortunately the patient died ten days later after hospitalization. A necropsy exam revealed pituitary gland with increased dimensions (2.5 x 2.0 cm). Histopathological findings revealed tumor proliferation in pituitary gland. The neoplasm showed invasion to the nervous parenchyma and metastatic foci between the brain lobes. Immunohistochemistry was positive for keratin and neuron-specific enolase and negative for epithelial membrane antigen, S-100 protein, glial fibrillary acidic protein, estrogen receptor, CD34, chromogranin, somatostatin, and ACTH. The clinical, histopathological and immunohistochemistry findings supported the diagnosis of primary pituitary carcinoma. Discussion: There is lack information regarding pituitary carcinoma prevalence in dogs, and little is known about its pathological and clinical features. The patient showed a shorter survival time (30 days after the onset of clinical signs) for a non-hormonally functional tumor that presented with acute onset of neurological signs due to local effect of an expanding mass, also described in others pituitary carcinoma reports. It was observed a metastatic focus of pituitary neoplasia between cerebral hemispheres, leading us to conclude to be a pituitary carcinoma. Adjacent infiltration was noticed by the presence of neoplasm invasion to the synoptic nervous parenchyma and metastatic foci between the brain lobes as well as the presence of a non-delimited nodular area of neoplastic implantation between the cerebral hemispheres, and optic nerve compromised by neoplasm cells. The data reported here showed that a negative ACTH receptor in neoplasm with 10% Ki-67 proliferation index with no history of clinical signs of pituitary-dependent hyperadrenocorticism (PDH). Pituitary adenocarcinomas are thought to be more often non-secretors. CT findings reveled a pituitary mass of 2.5 cm in vertical height suggesting a pituitary macrotumor although there is lack of description for pituitary carcinomas in veterinary literature. The animal had a fast deterioration of his clinical condition and quickly came to death, suggesting poor biological behavior of the tumor.
Keywords: adrenocorticotropic hormone; case report; dog; pituitary tumors